Optimizing parameter constraints: a new tool for Fisher matrix forecasts - Amendola, Luca; Sellentin, Elena (Monthly notices of the Royal Astronomical Society, 2016)
In a Bayesian context, theoretical parameters are correlated random variables. Then, the constraints on one parameter can be improved by either measuring this parameter more precisely - or by measuring the other parameters more precisely. Especially in the case of many parameters, a lengthy process of guesswork is then needed to determine the most efficient way to improve one parameter's constraints. In this short paper, we highlight an extremely simple analytical expression that replaces the guesswork and that facilitates a deeper understanding of optimization with interdependent parameters.